The energy storage mathematical models for simulation and comprehensive analysis of power system dynamics: A review. Part II; International Journal of Hydrogen Energy; Vol. 48, iss.15 - Razzhivin I. A. Igor Andreevich; Suvorov A. A. Aleksey Aleksandrovich; Ufa R. A. Ruslan Alexandrovich; Andreev M. V. Mikhail Vladimirovich; Askarov A. B. Alisher Bakhramzhonovich (2023, 2023)
Title screen